PENGARUH METODE DISCOVERY LEARNING TERHADAP KETERAMPILAN MENULIS TEKS CERITA PENDEK SISWA KELAS VII SMP NEGERI 4 PARIAMAN - Turrahmayani, Aisyia; Emidar, Emidar; Noveria, Ena (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
ABSTRACTÂ This article was written to describe the effect of discovery learning method on the skill of writing short story text of grade VII students of SMP Negeri 4 Pariaman. The data of this research is score of test resultof writing short story without using discovery learning method and using discovery learning method seventh grade students of SMP Negeri 4 Pariaman. Based on the results of the research, it can be concluded the following three points. First, the skill of writing short story text of grade VII students of SMP Negeri 4 Pariaman without using discovery learning method is in qualification Enough (C). the skill of writing short story text of grade VII students of SMP Negeri 4 Pariaman using discovery learning method is in good qualification (B). Third, based on the results of t-test, the alternative hypothesis (H1) is accepted at level siginificance 95% and degrees of freedom (dk) = n1 + n2 - 2 for tcount> ttable (5.69> 1.67). In other words, the skill of writing short story text of grade VII students of SMP Negeri 4 Pariaman using discovery learning method better than without using discovery learning method.Â Kata kunci: pengaruh, metode discovery learning, menulis teks cerita pendek